2022
DOI: 10.1111/inm.13035
|View full text |Cite
|
Sign up to set email alerts
|

Coping styles and mental health outcomes of community members affected by black summer 2019–20 bushfires in Australia

Abstract: The aim of this study was to investigate coping styles, posttraumatic stress, and mental health symptoms among a sample of community members affected by 2019–20 Australian bushfires. Using a convenience sampling approach, an online survey was used to assess a range of coping strategies, posttraumatic stress and symptoms of depression, anxiety, and stress among the affected community members of Black Summer bushfires. The results revealed that study participants reported moderate symptoms of depression and stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In line with other disaster research (Bryant et al, 2021; Usher et al, 2022), we provide further evidence that experiencing bushfire increases risk of psychological distress. As disasters become more frequent and extreme, robust policy and practice to support disaster resilience is essential, particularly given the immense pressure that mental health systems are currently experiencing (American Psychological Association [APA], 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with other disaster research (Bryant et al, 2021; Usher et al, 2022), we provide further evidence that experiencing bushfire increases risk of psychological distress. As disasters become more frequent and extreme, robust policy and practice to support disaster resilience is essential, particularly given the immense pressure that mental health systems are currently experiencing (American Psychological Association [APA], 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Age and higher PTSD symptoms predicted fewer positive resilience characteristics 5 years after the Canadian Fort McMurray Wildfire (Adu et al, 2022). In the year following the 2019–2020 Australian bushfires, high levels of psychological distress were recorded (Usher et al, 2022), but predictors have not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, avoidant coping strategies (e.g. drug and alcohol use to reduce stress) have been associated with higher psychological distress after a disaster (Usher et al, 2022 ). Yet, the role of psychosocial resources in shaping post-disaster mental health, especially in the long-term aftermath of disasters, remains understudied.…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 and ground-level ozone (O 3 ) exposure accounted for an estimated 250 excess deaths and 3490 hospitalizations in New South Wales and Victoria [11]. There were also substantial mental health impacts associated specifically with the smoke, including anxiety, depression, stress, and post-traumatic distress [12,13]. These health and wellbeing effects were magnified in children, especially those in vulnerable communities [14,15].…”
Section: Introductionmentioning
confidence: 99%